A study on relationship between severity of diabetic retinopathy and subclinical hypothyroidism - Borooah, Mitali; Phukan, Shobhana (International Journal of Research in Medical Sciences, 2017)
Background: Subclinical hypothyroidism (SCH) is defined as an asymptomatic condition characterized by normal serum levels of free thyroxine and elevated serum concentration of thyrotropin (>4.0µIU/ml). Association between diabetic retinopathy and SCH is unclear. Aim was to study the relationship between severity of diabetic retinopathy and SCH in patients of diabetic retinopathy with type 2 diabetes mellitus. Methods: 120 patients of diabetic retinopathy with known type 2 diabetes mellitus were taken and categorized them according to severity of diabetic retinopathy as per ETDRS classification. Serum thyrotropin (TSH) and free thyroxine (FT4) concentration were measured in all 120 patients. Patients with normal TSH and FT4 values are euthyroid patients and those with normal FT4 but TSH value >4µIU/ml are considered as having subclinical hypothyroidism. Severity of diabetic retinopathy is compared between the euthyroid and subclinical hypothyroid group. Results: Out of the 120 patients included in the study, 72 (60%) were male and 48 (40%) were female. 97 patients (80.83%) were Euthyroid and 23 patients (19.17%) had subclinical hypothyroidism. It was observed that prevalence of more severe form of diabetic retinopathy (severe NPDR and PDR) was higher in SCH group as compared to euthyroid group. Severity of diabetic retinopathy was compared with serum TSH level and it was seen that severity of diabetic retinopathy significantly increases with increase in serum TSH value. Conclusions: Patients with SCH had more severe form of diabetic retinopathy as compared to patients with euthyroidism. Severity of diabetic retinopathy significantly increases with increase in serum TSH value.